Biosecurity Adoption of Beef Cattle Farmers - Veronica Sri Lestari; Sitti Nurani Sirajuddin; Agustina Abdullah (Universitas Sebelas Maret, 2017)
The main objective of this research is to find the level of biosecurity adoption by beef cattle farmers. This research is conducted in Luwu regency, South Sulawesi, Indonesia. The data are collected from observation and interview using questionnaire. The sample is 31 beef cattle farmers who are selected using random sampling. There are 35 questions in the questionnaire that consist of management practice, sanitation, equipment, disease and disease prevention, and calf management. The data are analyzed descriptively using frequency distribution. The results revealed that the level of biosecurity adoption is 69.3%, and it is categorized as “high adopters”.